Fobias e transtorno de pânico em idosos atendidos pelo programa estratégia saúde da família do município de Porto Alegre, Rio Grande do Sul, Brasil - Silveira, Kenia Fogaça da (2014)
In addition to the worldwide increase in the geriatric population, is highlighting the high prevalence of mental disorders in the elderly also have a tendency to growth. We conducted a cross-sectional study with prospective data collection. The main objective is to study the prevalence and associations of specific phobias (SPP), social phobia (SP), agoraphobia (AGP) and panic disorder (PD) in a sample of elderly in the city of Porto Alegre, RS. Data collection occurred in two stages structured interviews. In addition to the estimates of prevalence of disorders, were performed tests to detect associations of the factors in a study of sociodemographic characteristics. Disorders with higher prevalence were SPP (17 %) and having ever AGP, covering 8.7% of the interviewed subjects. 4 % showed SP and 3.7 % of the elderly have PD diagnosis sometime in their lives. Older women had higher association with SPP, PD and AGP. Noticed other associations with sociodemographic data, but these, according to each specific disorder. It can be noticed that even within a category of diseases, conditions vary from each other and has its particularities associations. Thus, we need to be attentive to the singularities of each patient, and especially in the case of the elderly, as they are more likely to possess hidden diagnoses; like the Anxiety Disorders.